Plano de gerenciamento de resíduos sólidos de um shopping center de grande porte do Estado de Goiás - MARSARO, Gabriela Cavalcante Silva (2009)
The malls are large centers of consumption and leisure where the population find everything under the same roof, options for shopping, food and fun. The waste generation within these stores is big, especially in food. Most malls in Brazil does not have a plan for waste management, which possibly contributes to environmental problems and the reduction of life in landfills. Thus, this study aimed to develop a plan for managing solid waste from a large Shopping Center of the State of Goiás, to minimize, reuse and recycling of waste and the correct management of them. For this end, information was raised through interviews and site visits. The research was divided, basically, in diagnosis and prognosis (in other words, proposals for corrective measures). Diagnoses were evaluated in the waste-generating activities as well as the identification, classification and quantification of waste, and waste management practices used. The results indicated that the residue found in greatest quantity was the construction and demolition (137 t/ month), followed by organic material (75 t/ month). The paper also had a significant (8.5 t/ month). Except for the remains of cardboard, which is segregated, most of the potentially recyclable waste, which could still be traded, was found contaminated with organic waste and is therefore willing landfill in the Goiânia municipality. There was also no segregation of any kind regarding hazardous waste. Thus, some hazardous waste such as lamps with mercury vapor, are prepared along with other waste and improperly referred to the landfill. There Were found outside the waste containers, lack of capacity of them, casting the slurry and risks of contamination, therefore, in the same place where the waste is stored, the materials are discharged to supply the shops. As corrective measures, and alternatives were presented guidelines for the handling, collection, transport, storage and final disposal of waste. It was proposed the model of segregation into two groups: "recyclable materials" and "Organic and others." New containers were placed in selective shopping environments, along with informational posters. The points of loading and unloading (Pier) were retired and new containers were implanted selective. There was a significant change in the habits of officials and merchants who attended the training after the implementation of selective containers. However, for the operation of the plan, the segregation has to be done in an integrated manner, which still does not occur at the mall. The recyclable materials will be taken to a central sorting, which will be located in an area outside the mall. There, the waste will be segregated for better subsequent sale. For lamps, was located a container with its own specifications for the waste